The Role of Platelet-Rich Fibrin (PRF) in the Prevention of Medication-Related Osteonecrosis of the Jaw (MRONJ). (15th May 2021) - Miranda, Michele; Gianfreda, Francesco; Raffone, Carlo; Antonacci, Donato; Pistilli, Valeria; Bollero, Patrizio
Abstract : Dentoalveolar surgery is probably the major risk factor for MRONJ and for other complications following a tooth extraction, especially in patients affected by systemic diseases. The aim of this retrospective study is to evaluate whether a PRF plug inserted in the post extraction socket can prevent the onset of MRONJ. The patients were divided into two groups according to the surgical protocol that included the insertion or not of the PRF following the extraction and all the anamnestic, and clinical data were analyzed. In the control group, 5 patients developed MRONJ (19.23%) while in the study group, any case of MRONJ was reported. In the control group, patients who developed MRONJ had a CTX with less than 100 pg/mL (5 high-risk patients, Spearman's rank r = .547, p < .001 ). The use of platelet concentrates in patients with high risk of MRONJ is a user-friendly technique with an excellent cost-benefit ratio in oral surgery.